The effects of supply shocks in the market for apprenticeships : evidence from a German high school reform - Mühlemann, Samuel [Verfasser]; Pfann, Gerard A. [Verfasser]; Pfeifer, Harald [Verfasser]; Dietrich, Hans [Verfasser] (My University, 2018)
"This paper studies the effects of the G8 high school reform in Germany. The reform reduced minimum duration to obtain a high school degree (Abitur) from 9 to 8 years. First, we present a simple model based on a CES technology with heterogeneous inputs to conjecture possible effects of a supply shock of high education apprenticeships. Implementation of the reform across states (Länder) has been realized in different years. A difference-in-differences estimation strategy is used to identify the effects of one-time supply shock in market for high-educated apprentices. Training firms almost fully and immediately absorbed the additional supply of high school graduates in the apprenticeship market. No evidence is found for substitution effects between low and high education apprenticeships. The model explains that these effects may be due to sticky and too low collectively bargained wages for high education apprenticeships relative to their productivity. This renders the market for apprenticeships inefficient." (Authors' abstract, BIBB-Doku)
Parallel veröffentlicht als "IZA DP No. 11264", http://ftp.iza.org/dp11264.pdf
Keywords: S 1.1 Allgemeinbildende Schule; P 2.1 Schulabgänger; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; Gymnasium; Schulreform; Schulabgänger; Berufseinmündung; Erste Schwelle; Einflussfaktor; Schulabschluss; Substitutionseffekte; Regressionsanalyse